MODELOWANIE – UMIEJĘTNOŚĆ CZY SZTUKA? - Kluszczyński, Krzysztof (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The work is an attempt to define the essence of modelling process, which plays such an important and key role in the development of science and technology. The author points to the fundamental characteristics of a good model and conditions for assessing its correctness resulting from the model usefulness to solve specific engineering tasks. To make considerations and conclusions more convincing, the author repeatedly refers to various genres of art: painting, graphics, architecture, music and applied arts, to clearly expose the keynote telling that modelling in engineering is a creative process, characterized by the same features as the creative process associated with the creation of works of art. Examples illustrating the principles of modelling as well as the similarities and parallels between the works of engineering of various nature and works of art were taken from various web sources: Wikipedia, materials from the collections of the author and library of the Academy of Music in Katowice, from his own scientific work from different periods of his activity, from the results of research available by other scientists, among others, prof. Andrzej Demenko, as well as from the monograph of J. Turowski “Electromagnetic calculations of machine parts and electrical appliances”. Some of them have been prepared specially for this the article by Marcin Szczygieł, Marek Kluszczyński and Wojciech Pytel.